High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Spectrin: Structure, function and disease - Rui Zhang; ChenYu Zhang; Qi Zhao; DongHai Li (Science China Life Sciences, 2013)

Molecular Cloning and Transcriptional Analysis of the Putative AGAMOUS Homolog AcAG in Onion (Allium cepa) - Hong-You Li; Rui Zhao; Chan Wang; Li-Ying Zhang; Hong Zhao; Yong-Qin Wang (Plant Molecular Biology Reporter, 2013)

Overexpression of PeHSF mediates leaf ROS homeostasis in transgenic tobacco lines grown under salt stress conditions - Zedan Shen; Mingquan Ding; Jian Sun; Shurong Deng; Rui Zhao; Meijuan Wang; Xujun Ma; Feifei Wang; Huilong Zhang; Zeyong Qian; Yue Hu; Rui Yu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

Expression and Functional Significance of Ezrin in Human Brain Astrocytoma - Jie Mao; Xian-rui Yuan; Shan-shui Xu; Xiao-chun Jiang; Xin-tong Zhao (Cell Biochemistry and Biophysics, 2013)

Sorption Behavior of Phosphate on an MSWI Bottom Slag and Sewage Sludge Co-sintered Adsorbent - Suyang Ge; Hui Zhang; Hai Ye; Houhu Zhang; Keqiang Zhao; Qinfang Sun; Rui Wu; Wenping Cao (Water, Air, & Soil Pollution, 2013)

The Role of Autophagy Dysregulation in Manganese-Induced Dopaminergic Neurodegeneration - Jianbin Zhang; Rui Cao; Tongjian Cai; Michael Aschner; Fang Zhao; Ting Yao; Yaoming Chen; Zipeng Cao; Wenjing Luo; Jingyuan Chen (Neurotoxicity Research, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Vertical Distribution of Ammonia-Oxidizing Archaea and Bacteria in Sediments of a Eutrophic Lake - Dayong Zhao; Jin Zeng; Wenhua Wan; Huidi Liang; Rui Huang; Qinglong L. Wu (Current Microbiology, 2013)

Perfectly matched layer-absorbing boundary condition for finite-element time-domain modeling of elastic wave equations - Jian-Guo Zhao; Rui-Qi Shi (Applied Geophysics, 2013)

Litorilituus sediminis gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Yan Wang; Rui Zhao; Shiqi Ji; Zhao Li; Tong Yu; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Roseovarius marisflavi sp. nov., isolated from an amphioxus breeding zone in the coastal region of the Yellow Sea, China - Zhao Li; Rui Zhao; Shiqi Ji; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Genome-wide identification and transcription analysis of soybean carotenoid oxygenase genes during abiotic stress treatments - Rui-Kai Wang; Chun-E Wang; Yun-Yan Fei; Jun-Yi Gai; Tuan-Jie Zhao (Molecular Biology Reports, 2013)

Determination of oxidized scytonemin in Nostoc commune Vauch cultured on different conditions by high performance liquid chromatography coupled with triple quadrupole mass spectrometry - Juanjuan Chen; Lijuan Zhao; Jilin Xu; Rui Yang; Shan He; Xiaojun Yan (Journal of Applied Phycology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Atrazine biodegradation by Arthrobacter strain DAT1: effect of glucose supplementation and change of the soil microbial community - Shuguang Xie; Rui Wan; Zhao Wang; Qingfeng Wang (Environmental Science and Pollution Research, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Mineralogical constraints on the origin of Neoproterozoic felsic intrusions, NW margin of the Yangtze Block, South China - Ze-Rui Liu; Jun-Hong Zhao (International Geology Review, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Quantitative assessment of the associations between MTHFR C677T and A1298C polymorphisms and risk of fractures: a meta-analysis - Rui Bai; Wanlin Liu; Aiqing Zhao; Zhenqun Zhao; Dianming Jiang (Molecular Biology Reports, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Contribution of mantle components within juvenile lower-crust to collisional zone porphyry Cu systems in Tibet - Zengqian Hou; Yuanchuan Zheng; Zhiming Yang; Zongyao Rui; Zhidan Zhao; Sihong Jiang; Xiaoming Qu; Qinzhong Sun (Mineralium Deposita, 2013)

Carbon and oxygen isotope stratigraphy of the oxfordian carbonate rocks in Amu Darya basin - Rongcai Zheng; Yanghui Pan; Can Zhao; Lei Wu; Renjin Chen; Rui Yang (Journal of Earth Science, 2013)

Litoribacillus peritrichatus gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Rui Zhao; Shiqi Ji; Yan Wang; Tong Yu; Zhao Li; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Pollen morphology and ontogeny of Maianthemum bifolium (L.) F.W. Schmidt in China - Bing-Xiao Chen; Chun-Hai Zhao; Yun-Yun Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2013)